2003
DOI: 10.1246/cl.2003.498
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectra, Crystal Polymorphism, and Structure of a Prototype Ionic-liquid [bmim]Cl

Abstract: A prototype ionic-liquid [bmim]Cl shows crystal polymorphism, having two crystal forms, Crystal (1) and Crystal (2), characterized by distinct X-ray powder patterns and Raman spectra. Two sets of characteristic Raman bands of Crystals (1) and (2), which are mutually exclusive with each other, do coexist in the spectrum of liquid [bmim]Cl. It seems that two distinct structures of the [bmim]+ ion, one corresponding to that in Crystal (1) and the other to that in Crystal (2), exist simultaneously in the ionic liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
250
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(265 citation statements)
references
References 6 publications
13
250
1
1
Order By: Relevance
“…As they stand, these results support the claims of Ref. 44 but, due to the small energy difference, the possibility of a phase transition between the two structures upon increasing temperature is re-instated, in agreement with the classical force field results of Jayaraman and Maginn. 46 Electronic energy gaps at the -point of the Brillouin zone are similar for the two structures.…”
Section: B Polymorphism Of [Bmim][cl]supporting
confidence: 90%
See 1 more Smart Citation
“…As they stand, these results support the claims of Ref. 44 but, due to the small energy difference, the possibility of a phase transition between the two structures upon increasing temperature is re-instated, in agreement with the classical force field results of Jayaraman and Maginn. 46 Electronic energy gaps at the -point of the Brillouin zone are similar for the two structures.…”
Section: B Polymorphism Of [Bmim][cl]supporting
confidence: 90%
“…In one of the experiments, carried out at 44, namely that the monoclinic structure was stable and the orthorhombic one metastable. These contrasting interpretations led to a controversy that is still open, and also to the notion that this system may actually offer different polymorphic alternatives for the crystalline phase.…”
Section: B Polymorphism Of [Bmim][cl]mentioning
confidence: 99%
“…[7][8][9][10] From the Raman spectroscopic study of 1-butyl-3-methyl imidazolium chloride ([BMIM][Cl]), Hayashi et al found that two different local conformations of bulk ionic liquid can coexist in the crystal, which would give a clue to understand why RILs exist as liquid at room temperature. 11 This report was supported by X-ray studies which found two local structures can coexist in RILs. 12, 13 Calculations that followed suggested that the above cation conformation change would alter the position of the anion and change the interaction between the anion and the cation in 1-alkyl-3-methylimidazolium halide ionic liquids.…”
Section: Introductionmentioning
confidence: 54%
“…For example, Hamaguchi's group used Raman spectral analysis to show for the first time that two distinct conformational structures of the imidazolium cation exist simultaneously in the IL state. 20,21 These investigators also obtained evidence of mesoscopic local structure in ILs by means of coherent anti-Stokes Raman scattering measurements. 22 Iwata et al investigated the importance of local structures in reaction dynamics by measuring the vibrational cooling rates of the excited state of trans-stilbene in ILs by picosecond time-resolved Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 96%